A Study on Spatial Distribution and Characteristics of Moving Companies - Seo, Dae Hyun; Kim, Kabsung (Scientific Research, 2018)
The purpose of this study is to propose a method of establishing demand zone in the estimation of industrial complex needs. Demand estimates of existing industrial complexes are mainly based on survey method, which leads to excessive or underestimated demand depending on the extracted samples. Therefore, it has been argued that there is a need to analyze what movements the companies actually show. In this study, based on the status of about 450,000 companies included in the Hankyung Business Yearbook, the company DB book in Korea, each company analyzed the movement and the moving area by city, and based on this, the O-D table was created. This study will empirically validate the previous demand of the enterprises and provide information related to the establishment of the demand for the industrial complex in the future, which will contribute to the estimation of the actual demand of the industrial complex.
Keywords: Industrial Complex; Industrial Land Use; Spatial Distribution of Companies; Characteristics of Companies; Company Movement